Theodyceal's Message of The Isenheim Altarpiece - Piecuch, Joachim (Studia Warmińskie, 2020)
The article contains the ideological and aesthetic analysis of the retabolic altar from Isenheim by M. Grünewald. The altar consists of a sequence of images. They present various themes. The aim of the article is to indicate the presence of the theodycelan problem as the main thread. A number of topics were identified in the study of images. These are not only theological but also anthropological and philosophical topics. These themes take the form of a question about conditio humana. The research took into account the wide historical and socio-existential context of creating images. It provides a hermeneutic key for its deep interpretation. The subject of detailed analysis are the representations contained in individual scenes of the image sequences. They are arranged in a specific order, aimed at bringing comfort and hope to the inhabitants of the monastery hospital in Isenheim, who suffer from ergotism. Therefore, the altar was not only a liturgical function. It also contained a saving message for people struggling with the question of the meaning of suffering. He gave the opportunity to identify those who suffered with the characters depicted in the pictures.